Development and Physicochemical properties of Breadfruit (Artocarpus altilis) Resistant Starch Bread - Zarinah, Zakaria; Norshazila, Shahidan; Napisah, Hussin (2018)
This study aims to produce breadfruit-resistant starch (BRS) bread with resistant starch concentration levels of 5%, 10% and 15%, and determine the physicochemical properties of the BRS bread produced. This study involved two major phases which were the breadmaking process and physicochemical analysis. A straight-dough method was applied during the preparation of bread, and the data obtained were statistically analyzed using the SPSS software. The results showed that the moisture content of the control bread was higher compared to the moisture content of the breadfruit-resistant starch (BRS) bread, and the BRS bread had a lower volume compared to the control bread. For texture analysis, there was no significant difference (p>0.05) in terms of hardness, springiness and chewiness between all samples of bread involved. Both the crumb and crust parts of the bread samples showed a decrease in the lightness color due to the presence of BRS and the occurrence of the Maillard reaction. As conclusion, the obtained results in this study are useful for the bakery and food industries when the functional ingredient is used in products and BRS bread that produced might be assumed as one of healthy fortified bread.